Mediation Empowerment in Resolution of Civil Claims in State Court - Hariadi Hariadi (IHSA Institute, 2023)
Mediation is a way of resolving disputes through a negotiation process to obtain an agreement between the parties assisted by a mediator as a facilitator, the provisions of which are regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in District Courts. Mediation in court is the institutionalization and empowerment of peace (court-connected mediation) with the philosophical basis of Pancasila which is the basis of the Indonesian State, especially the fourth precept